Analisis Kepuasan Pengguna Pada SINTAK STT Indonesia Tanjung Pinang Menggunakan Pieces Framework - Rohmaini, Rohmaini; Zulfachmi, Zulfachmi; As Saidah, Muthiah; Saputra, Aggry (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
The SINTAK Reporting Information System at STT Indonesia Tanjung Pinang is a system used to record students' academic activity transcripts, which serve as a mandatory requirement for the final examination process, with a minimum score of 60 points. However, in its implementation, SINTAK still has several features that can be further developed to enhance user convenience. Additionally, an analysis of user satisfaction with this system has been conducted using the Pieces Framework. This study aims to analyze user satisfaction levels regarding SINTAK and identify features that need improvement. The research employs a qualitative approach with descriptive analysis and an inductive method. Data collection methods include observation, interviews, literature review, and questionnaire distribution using a purposive sampling technique involving 87 respondents who are system users. The results indicate that the six variables in the Pieces Framework received average scores reflecting user satisfaction: performance (3.75, SATISFIED category), information & data (3.67, SATISFIED category), economic (3.51, SATISFIED category), control & security (3.71, SATISFIED category), efficiency (3.87, SATISFIED category), and service (3.79, SATISFIED category). These findings suggest that while SINTAK has met user needs, there are opportunities for further development to improve the system's effectiveness and efficiency.